Creative thinking and its relationship to visual field and visual speed among goalkeepers of the Iraqi Handball Premier League - Alwan, Saleemah Abdullah (SPORT TK-EuroAmerican Journal of Sport Sciences, 2022)
The aim of this study was to identify the level of creative thinking and the level of visual field of vision and its speed among goalkeepers. The study was also aimed to identify the relationship between these factors. The researcher used the descriptive approach in the correlative research method. This study involved a sample of 10 goalkeepers participating in the local championship of Iraqi clubs in the Premier League held in Sulaymaniyah Governorate, Kurdistan Region of Iraq. Statistical analysis was done using SPSS 26.0. The results of our study showed that creative thinking directly affects the visual field of vision and inversely to the visual reaction of goalkeepers in the Premier League handball clubs. The higher the creative thinking is, the degrees of their visual vision will increase and the time of their visual reaction will reduce. It is necessary to establish the improvement of creative thinking as an important psychological factor in the training units in the Premier League handball clubs, and also to increase the coaches’ experiences on improving it by gathering the physical and skill exercises of the goalkeepers.